Isolating N400 as neural marker of vocal anger processing in 6–11-year old children - Chronaki, Georgia (Dev Cogn Neurosci, 2011)
INTRODUCTION: Vocal anger is a salient social signal serving adaptive functions in typical child development. Despite recent advances in the developmental neuroscience of emotion processing with regard to visual stimuli, little remains known about the neural correlates of vocal anger processing in childhood. This study represents the first attempt to isolate a neural marker of vocal anger processing in children using electrophysiological methods. METHODS: We compared ERP wave forms during the processing of non-word emotional vocal stimuli in a population sample of 55 6–11-year-old typically developing children. Children listened to three types of stimuli expressing angry, happy, and neutral prosody and completed an emotion identification task with three response options (angry, happy and neutral/‘ok’). RESULTS: A distinctive N400 component which was modulated by emotional content of vocal stimulus was observed in children over parietal and occipital scalp regions—amplitudes were significantly attenuated to angry compared to happy and neutral voices. DISCUSSION: Findings of the present study regarding the N400 are compatible with adult studies showing reduced N400 amplitudes to negative compared to neutral emotional stimuli. Implications for studies of the neural basis of vocal anger processing in children are discussed.